Bacteriocins: Recent Trends and Potential Applications. Issue 5 (3rd April 2016) - Bali, Vandana; Panesar, Parmjit S.; Bera, Manab B.; Kennedy, John F.
Abstract : In the modern era, there is great need for food preservation in both developing and developed countries due to increasing demand for extending shelf life and prevention of spoilage of food material. With the emergence of new pathogens and ability of micro-organisms to undergo changes, exploration of new avenues for the food preservation has gained importance. Moreover, awareness among consumers regarding harmful effects of chemical preservatives has been increased. Globally, altogether there is increasing demand by consumers for chemical-free and minimal processed food products. Potential of bacteriocin and its application in reducing the microbiological spoilages and in the preservation of food is long been recognized. Bacteriocins are normally specific to closely related species without disrupting the growth of other microbial populations. A number of applications of bacteriocin have been reported for humans, live stock, aquaculture etc. This review is focused on recent trends and applications of bacteriocins in different areas in addition to their biopreservative potential.